The Impact of Friendship Environment on Adolescent Emotional Development - Deannopel, Nesha Kirani; Z, Sri Putri Rahayu; Jie, Lie (Yayasan Minang Darussalam, 2022)
The Influence of The Friendship Environment On The Emotional Development Of Youth. The method used in this study is a qualitative research that is library research, using journals, and articles related to the influence of the friendship environment on the emotional development of adolescents. Emotions in each individual have a different emotional response. We can see this from how individuals express their emotional feelings, for example, when they feel sad, there are teenagers who show their sadness by crying bitterly, there are also those who only express sad emotions by being silent, gloomy, and making them not want to do anything. Based on the results of reviewing and analyzing journals related to the title, it can be concluded that the influence of the friendship environment on the emotional development of adolescents is very influential because during adolescence. Therefore, the influence of friendship will have a greater impact on the individual than the influence that comes from the family environment. So it is necessary to have an individual stand and also be good at choosing healthy friendships so that they can support each other's emotional development efficiently and continuously. In this journal, which is sourced from several journals that have been reviewed, there are still many shortcomings in each discussion, especially in the minimizing section so that there are no obstacles to the emotional development of adolescents themselves. Therefore, for further researchers who are interested in raising the theme of exuberance, it is hoped that this section will be more emphasized.